Evaluating the use of lecture capture using a revealed preference approach. (July 2016) - Elliott, Caroline; Neal, David
This article discusses the introduction of lecture capture technology on a large undergraduate module with diverse student cohorts. The literature has, so far, relied on surveying students to discover their use of the technology or attempted to quantify the impact of watching lecture recordings on assessment performance. Alternatively, the principal contribution of this article is an evaluation of the use of the recorded lectures using a revealed preference approach. Specifically, we identify to what extent students watched lecture recordings, rather than simply claimed to watch them, when asked to provide comments on the technology. Data indicate the number of distinct students who watched recordings, the frequency with which they watched recordings, the average length of viewings as well as the time of the day when lectures were viewed. We monitored viewings over two academic years, identifying 'spikes' in the number of viewings in the days before tests, as well as regularities in the viewing patterns across the 2 years. We analyse the data to assess the extent to which students used the recordings, how and when they watched the recordings. We conclude that the students value lecture recordings, making more extensive use of the recordings than has been identified in the literature, to date. Ultimately, lecture recordings are suggested to offer valuable support for students' independent study.